2016
DOI: 10.1021/acs.joc.5b02793
|View full text |Cite
|
Sign up to set email alerts
|

Stereocontrolled Solid-Phase Synthesis of Phosphate/Phosphorothioate (PO/PS) Chimeric Oligodeoxyribonucleotides on an Automated Synthesizer Using an Oxazaphospholidine–Phosphoramidite Method

Abstract: Stereocontrolled solid-phase synthesis of phosphate/phosphorothioate chimeric oligodeoxyribonucleotides (PO/PS-ODNs) was achieved by integrating the conventional phosphoramidite method into a previously developed oxazaphospholidine method for the stereocontrolled synthesis of P-chiral oligonucleotides. P-Stereodefined PO/PS-ODNs with mixed sequences (up to 12-mers) were obtained in good yields and high stereoselectivities by reacting different combinations of monomers (conventional phosphoramidites/diastereopu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
11
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
6
2
1

Relationship

3
6

Authors

Journals

citations
Cited by 15 publications
(11 citation statements)
references
References 63 publications
0
11
0
Order By: Relevance
“…We previously reported an oxazaphospholidine approach for the stereocontrolled synthesis of PS-oligonucleotides. This approach is a type of phosphoramidite method whose features include the use of oxazaphospholidine monomer units, , whose phosphorus atom is in a stereocontrolled manner, derived from optically pure aminoalcohols, and N -cyanomethylpyrrolidinium triflate (CMPT), an acidic activator with low nucleophilicity. Mainly on the basis of the oxazaphospholidine approach, a few groups clearly revealed that each stereoregular PS oligonucleotide is significantly different in its properties, including the affinity to its complementary DNA and RNA, nuclease resistance, and RNase H activity. ,, Quite recently, another synthetic strategy has also been reported to construct stereoregular PS-DNA backbone using P­(V)-based reagents, which is different from conventional phosphoramidite chemistry . Some stereoregular PS nucleic acid therapeutics are still undergoing clinical trials, and therefore, stereoregular PS-oligonucleotides have the potential to be the next gold standard as nucleic acid therapeutics.…”
Section: Introductionmentioning
confidence: 99%
“…We previously reported an oxazaphospholidine approach for the stereocontrolled synthesis of PS-oligonucleotides. This approach is a type of phosphoramidite method whose features include the use of oxazaphospholidine monomer units, , whose phosphorus atom is in a stereocontrolled manner, derived from optically pure aminoalcohols, and N -cyanomethylpyrrolidinium triflate (CMPT), an acidic activator with low nucleophilicity. Mainly on the basis of the oxazaphospholidine approach, a few groups clearly revealed that each stereoregular PS oligonucleotide is significantly different in its properties, including the affinity to its complementary DNA and RNA, nuclease resistance, and RNase H activity. ,, Quite recently, another synthetic strategy has also been reported to construct stereoregular PS-DNA backbone using P­(V)-based reagents, which is different from conventional phosphoramidite chemistry . Some stereoregular PS nucleic acid therapeutics are still undergoing clinical trials, and therefore, stereoregular PS-oligonucleotides have the potential to be the next gold standard as nucleic acid therapeutics.…”
Section: Introductionmentioning
confidence: 99%
“…Most of the aforementioned therapeutic oligonucleotides approved by the U.S. Food and Drug Administration (FDA) or currently under clinical trials utilize phosphorothioate modifications to improve the metabolic stability and cellular uptake. , The traditional synthesis of phosphorothioate oligonucleotides based on phosphoramidites affords a mixture of stereoisomers. Recently, the stereogenic synthesis of phosphorothioate oligonucleotides has been significantly improved, which will have huge impacts on future therapeutic developments.…”
mentioning
confidence: 99%
“…These results were consistent with previous reports and the differences in the properties between the two diastereomers. 7,8,11,34,40 Moreover, the DT m values between the PO/(Rp)-PS-DNAs and the PO/(Sp)-PS-DNAs were different depending on the substituents on the C-5 position. In the case of dCG(U PS ) 8 CG (4a) and dCG(T PS ) 8 CG (4b), the DT m values between the PO/(Rp)-PS-DNAs and PO/(Sp)-PS-DNAs were relatively small, 2.8 C and 2.9 C, respectively.…”
Section: Uv Melting Analysismentioning
confidence: 99%